The role of the Soviet Union in the Second World War in British history textbooks - Evgeni S. Pankov (Научно-аналитический вестник Института Европы РАН)
The article analyzes the representation of the role of the USSR in World War II in British history textbooks: what is underscored is the great powers’ diplomatic rivalry in the pre-war period; the «turning point» in the war; the general assessment of the Soviet people’s contribution to the victory. The aim of the study is to identify the subjects that are characterized by consensus among the authors of textbooks and the events that cause disagreement among them. The study is based on a qualitative content analysis of ten textbooks published after 2000, using the comparative method. The article concludes that the representation of the role of the USSR in the war is characterized by duality: on the one hand, the Soviet Union is seen as a member of the Anti-Hitler Coalition that made a decisive contribution to the victory; on the other hand, it is seen as the embodiment of totalitarianism, which Britain fought against throughout the 20th century. At the same time, events that contradict this duality are not shown in textbooks. In this connection, without denying the contribution of the Soviet people to the defeat of Hitler’s troops, the authors of textbooks raise the question of the role of Soviet diplomacy in unleashing the conflict – here the range of positions is much more diverse. It is the first attempt to comparatively analyze the content of British history textbooks in the context of the unfolding «memory wars» between Russia and the West. In this regard, the practical usefulness of the work consists in the possibility to apply its results in identifying potential areas of rapprochement between Moscow and London for overcoming «historical traumas».